KEKERASAN SIMBOLIK SUAMI TERHADAP ISTRI DALAM PERSPEKTIF BUDAYA JAWA Studi di Kampung Urban Yogyakarta - Basilica Dyah Putranti (Research Centre for Population, Indonesian Institute of Sciences, 2007)
One important thing that has not been explored from the previous researches is how the violence toward wives both in the from of overt actions and the invisible actions, connected to masculine domination from socio-:-cultural frames. This study will explored these connections focuses on the contemporary Java as cultural context. As especially research question is how the violence toward wives understands by women subjective and the people at urban village, Yogyakarta, thus far it is institutional by the social-culture system.Keywords: Symbolic violence, Masculine culture, Kampung urban